Peran Environmental Knowledge Memoderasi Pengaruh Green Supply Chain Management dan Enterprise Resources Planning Terhadap Sustainability Performance - Pangestu, Juan; Akwila, Karvicha (Dinasti Research, 2024)
The Green Supply Chain Management (GSCM) process is widely associated with its contribution to the company's sustainability performance. The GSCM process will also be associated with an integrated Enterprise Resource Planning (ERP) system that will have an impact on achieving sustainability performance. The importance of environmental awareness from manufacturers to direct their business processes that are beneficial to the environment in the long term. This study aims to analyze the effect of Green Supply Chain Management and Enterprise Resource Planning on Sustainability Performance, then this study also analyzes the role of Environmental Knowledge as a moderation of the influence of Green Supply Chain Management and Enterprise Resource Planning on Sustainability PerformanceThe analysis method used is path analysis with the pattern of relationships between independent variables in this study being correlative and causal. Researchers use primary data collection techniques because this study will use a questionnaire. This questionnaire technique is also a data collection technique by providing a set of written questions or statements to respondents. Based on the results of this study, it shows that Green Supply Chain Management has a significant effect on Sustainable Performance, Enterprise Resource Planning does not have a significant effect on Sustainable Performance, Environmental Knowledge strengthens the influence of Green Supply Chain Management on Sustainable Performance, Environmental Knowledge does not strengthen the influence of Enterprise Resource Planning on Sustainable Performance.